A Interdisciplinaridade do Cálculo: aplicações do Cálculo Diferencial e Integral I - SILVA, Evelyn Sabrina Silva e (2023)
This Course Conclusion Work presents an material to support the teaching of the calculation, has as its theme the Interdisciplinarity of Calculus and the objective of studying Differential and Integral Calculus I and also show its applicability indifferent areas, as a motivationtool, to answer questions such as for example, "by that I need to learn that?" and highlight its relevance, solving contextualized questions of books for teaching calculus in graduations and ENADE (National Student Performance Exam) exams, used to evaluate higher education courses. For this we will make a brief historical summary of differential and integral calculus, its importance to society today and we will present the calculation concepts necessary to understand the resolutions of the problems presented. The difficulty of students in the calculation disciplines is recognized by several authors, teachers and pedagogues and some many factors are indicated as contributors to poor performance in courses that have calculus in their grid. As a result of the above, this work develops an alternative material to support the teaching of calculus, addressing the main concepts of Differential and Integral Calculus and solving problems of other areas and sciences. We will also show some behaviors of functions and graphics with the help of Geogebra Software, which is a great aid in the modeling of teaching and practical development of content in the classroom.